Resonant Liquid Motion in Marine Hydrodynamics. (2015) - Faltinsen, O.M.
Abstract: Sloshing in ship tanks and piston-mode resonance in moonpools are discussed. A nonlinear analytically based multimodal method is used to explain how sloshing depends on the liquid depth in 2D flow. The importance of 3D flow with possible swirling and chaos for nearly square base tanks as well as vertical cylindrical and spherical tanks is emphasized. The many physical phenomena involving fluid mechanic and thermodynamic parameters as well as hydroelasticity effecting slamming load effects and associated scaling from model to full scale for LNG are discussed.